High-sensitivity cardiac troponin T for early prediction of evolving non-ST-segment elevation myocardial infarction in patients with suspected acute coronary syndrome and negative troponin results on admission - Giannitsis, Evangelos; Becker, Meike; Kurzhals, Kerstin; Hess, Georg; Zdunek, Dietmar; Katus, Hugo (Clinical chemistry, 2010)
Background: We sought to determine the diagnostic performance of the new high-sensitivity cardiac troponin T (hs-cTnT) assay for early detection of non-ST-segment myocardial infarction (NSTEMI) in patients with acute coronary syndrome.Methods: We enrolled patients with retrospectively confirmed unstable angina or NSTEMI and an initially negative cTnT concentration and compared the performance of baseline concentrations and serial changes in concentration within 3 and 6 h. Percentage change criteria included ≥20% δ change and ROC-optimized value.Results: Based on the standard fourth-generation cTnT result of ≥0.03 μg/L, an evolving NSTEMI was diagnosed in 26 patients, and 31 patients were classified as having unstable angina. With the use of the hs-cTnT assay at the 99th-percentile cutoff, the percentage of NSTEMI cases detected increased gradually from 61.5% on presentation to 100% within 6 h, and the overall number of MI diagnoses increased by 34.6% (35 vs 26 cases). A δ change ≥20% or ≥ROC-optimized value of >117% within 3 h or ≥243% within 6 h yielded a specificity of 100% at sensitivities between 69% and 76%. The standard cTnT at the 99th percentile was less sensitive than hs-cTnT for early diagnosis of MI on presentation, and follow-up samples obtained within the initial 3 h demonstrated very low specificity of cTnT compared with hs-cTnT.Conclusions: The high-sensitivity cTnT assay increases the number of NSTEMI diagnoses and enables earlier detection of evolving NSTEMI. A doubling of the hs-cTnT concentration within 3 h in the presence of a second concentration ≥99th percentile is associated with a positive predictive value of 100% and a negative predictive value of 88%.